IMPLEMENTASI SISTEM INFORMASI PRESENSI KEHADIRAN SISWA MENGGUNAKAN FINGERPRINT TERINTEGRASI DENGAN SMS GATEWAY - Arie Atwa Magriyanti; Zaenal Mustofa (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
Along with the development of computer technology and information technology, the data processing system functions to provide services and meet the demands of various parties (Wibowo, 2013). One form of data processing is the presence system required by the school. The benefits of advances in information technology can directly provide advantages for institutions or schools. The attendance information system is able to provide convenience for the manager to carry out attendance activities as well as provide accurate information to parents of students. The attendance system is also carried out by the Jumo Kedungjati Islamic Vocational School, but it is still manual. Jumo Kedungjati Islamic Vocational School is located on Jalan. Kauman No. 9 Jumo Village, Kedungjati District, Grobogan Regency, Central Java. This school does not yet have an information system for computerized student attendance data processing. Student attendance is generally done with the student's signature on the attendance sheet. The attendance system can run well, if the recording of student attendance is effective and efficient. The attendance of students at Jumo Islamic Vocational School is used at this time by being given a sheet to be signed by each student to take part in teaching and learning activities. From the existing problems, the authors designed a student attendance information system with a fingerprint-based SMS gateway. This attendance system was created using Visual Basic 6 programming language, MySQL database, fingerprint tool to detect student fingerprints and Wavecom modem for SMS Gateway. This study uses the Research and Development (R&D) method, which is a method for creating new products or improving existing products, which are expected to provide better service with the required reports as expected.